(untitled) - Enger, Eldon D (Dubuque, Iowa, 1997)
The book begins with a discussion of the meaning, purpose, and future of biology as a scientific endeavor. It then covers biological concepts as an expanding spiral of knowledge. Thus, chemistry is followed by cell biology, cell division, genetics, ecology, evolution, anatomy and physiology, and the diversity and classification of living things
Keywords: Biology